The Post-Traumatic Growth Experience in Family Caregivers of People with Dementia: A Descriptive Qualitative Study - Wang Y; Gu Y; Qiu R; Long D; Sun N (Psychology Research and Behavior Management, 2025)
Yang Wang,1– 3 Yanhong Gu,1– 3 Ruxia Qiu,2 Dechao Long,1– 3 Na Sun2 1Nursing Department, Shanghai Fifth People’s Hospital, Fudan University, Shanghai, People’s Republic of China; 2School of Nursing, Fudan University, Shanghai, People’s Republic of China; 3Center of Community-Based Health Research, Fudan University, Shanghai, People’s Republic of ChinaCorrespondence: Yanhong Gu, Nursing Department, Shanghai Fifth People’s Hospital, Fudan University, No. 801 heqing Road, Minhang District, Shanghai, 200240, People’s Republic of China, Tel +86-18516261081, Email reddy_gu@163.comPurpose: To explore and illuminate the post-traumatic growth experience among family caregivers of people with dementia.Patients and Methods: Descriptive qualitative research was conducted using purposive sampling. Between June and October 2024, 19 family caregivers of dementia patients were selected from an outpatient clinic for memory disorders and a mental health center in Shanghai. The NVivo 20.0 software was used to organize and code the interview data, and the data were analyzed and thematically condensed using the directed content analysis method.Results: Four themes were identified, along with eleven sub-themes associated with them: cognitive-behavioral shift (transitioning family roles, recognizing disease characteristics, focusing on health management, and responding positively and effectively); personal strength enhancement (enhancing coping capacity, increased psychological resilience and increased responsibility); improved relationships with others (harmonizing in family relations and benefiting from social interactions); and changes in life perceptions (reshaping of values, and reconstructing the meaning of life).Conclusion: Family caregivers of people with dementia experience multifaceted post-traumatic growth after a traumatic event of disease diagnosis and patient caregiving. It is necessary to focus on positive psychological resources for family caregivers to improve the burden of caregiving. Future research should take measures to promote family caregivers’ positive perceptions, explore their own potential and strengths, and help them make full use of family and social support to enhance their post-traumatic growth.Keywords: older adult, dementia, informal caregivers, post-traumatic growth